ANALYSIS OF QUALITY OF LIFE AND COMPLIANCE LEVEL OF PULMONARY TB PATIENTS AND BODY MASS INDEX IN POST-TRANSFERENCE TREATMENT ANTI TUBERCULOSIS IN HOSPITAL dr. M HAULUSSY AMBON - Salama Sely; Yuly Peristiowati; Augustine (International Journal of Medical Science and Public Health Research, 2024)
Tuberculosis is the most common multi-systemic infection, with various types of manifestation and clinical description, lung is the most common location for developing tuberculosis disease (WHO, 2018). As many as 58% of cases of pulmonary TB occur in 3 (three) countries such as Southeast Asia. Based on profile Service Health Maluku Province, in 2021 number of invention Pulmonary TB cases Service Health (Health Office) of Maluku Province to end in 2019 it reached 6,379 people or by 0.35 percent of total population in the province the largest as 1.8 million people.This research uses a quantitative observational design with a cross sectional approach. With sample use systematic type Purposive sampling of 83 respondents. Data analysis using linear regression. Results test statistics show the most influential variable to level pulmonary tuberculosis treatment is a level indicator compliance with level significance sig 0.000. Based on the results of the Multiple Linear Regression analysis, it shows that with a p-value of 0.00 0 < 0.05, H 1 is accepted, so it is concluded that there is a simultaneous influence quality of life as well as the level of compliance of TB lung sufferers And body mass index on post treatment tb lung at DR M Haulussy Ambon Regional Hospital. ZENODO DOI:- https://doi.org/10.5281/zenodo.14038194